Efeito anti-hiperalgésico e anti-inflamatório dos complexos de inclusão de citral em β-ciclodextrina e hidroxipropil-β-ciclodextrina - Campos, Caio de Alcântara (2019)
Citral (CIT) is a monoterpene formed by the geranial and neral stereoisomers. CIT is the major compound of Cymbopogon citratus essential oil, known as “capim-limão”, and has demonstrated potential antihyperalgesic, anti-nociceptive and anti-inflammatory effects. However, CIT shows high volatility, low solubility in water and consequent low bioavailability, which limits its use. Therefore, the aim of this study was to prepare, characterize, evaluate cell viability, anti-hyperalgesic and anti-inflammatory effects of inclusion complexes of CIT on β-cyclodextrin (β-CD) and hydroxypropyl-β-cyclodextrin (HP-β-CD). Initially, physical mixture (PM) and freeze-dried inclusion (FD) complexes of CIT/β-CD and CIT/HP-β-CD were obtained in the molar ratio (1:1). The samples were characterized by DSC, TG/DTG, FTIR, XRD, SEM and the complexation efficiency were performed by HPLC. Cell viability assay was performed by rezasurin reduction technique in J774 macrophages cell line. The motor activity through rota rod apparatus, mechanical hyperalgesia and pleurisy induced by carrageenan were evaluated in mice. The complexation of CIT was evidenced with β-CD and HP-β-CD by the characterization techniques analyzed. The complexation efficiency of CIT/β-CD and CIT/HP-β-CD were 78.6% and 71.7%, respectively. The CIT, CIT/β-CD and CIT/HP-β-CD showed cell viability in macrophages and did not interfere in the motor activity of mice. Besides that, the samples demonstrated antihyperalgesic and anti-inflammatory activity due to reduction in total leukocytes and TNF-α levels. However, CIT/β-CD has better pharmacological effects among the three samples evaluated. Therefore, CIT/β-CD has potential for the development of products to treatment of inflammatory and painful reactions.